The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/gj.4857
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of aerosol optical and physical properties and implications for radiative effects over the semiarid region of Indo‐Gangetic Basin

Pratima Gupta,
Ashok Jangid,
Ranjit Kumar

Abstract: This study assesses the physical and optical properties and estimated the radiative forcing of aerosol at Agra over the Indo‐Gangetic Basin (IGB) during July 2016–December 2019 using black carbon (BC) mass concentration (AE‐33 aethalometer), data sets from satellite and model simulations. The optical properties of aerosol and radiative forcing have been measured by the Optical and Physical Properties of Aerosols and Clouds (OPAC) and Santa Barbara Discrete Ordinate Radiative Transfer Atmospheric Radiative Tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…Among the six discussed distributions, Weibull (3P) distribution provides the best fit to model the meteorological data from the satellite: flood prediction can be obtained from the proposed model. Gupta, Jangid, et al (2023) measured the physical and optical properties and estimated the radiative forcing of aerosols at Agra over the Indo-Gangetic Basin (IGB) where they revealed that the postmonsoon seasons had increased aerosol loading and significant changes in vertical distribution, which affected the heating rate in the summer season, boundary layer dynamics and convection. This study improves our understanding of the importance of aerosol heating rate over the IGB region because it can alter the temperature and modify the monsoon.…”
mentioning
confidence: 99%
“…Among the six discussed distributions, Weibull (3P) distribution provides the best fit to model the meteorological data from the satellite: flood prediction can be obtained from the proposed model. Gupta, Jangid, et al (2023) measured the physical and optical properties and estimated the radiative forcing of aerosols at Agra over the Indo-Gangetic Basin (IGB) where they revealed that the postmonsoon seasons had increased aerosol loading and significant changes in vertical distribution, which affected the heating rate in the summer season, boundary layer dynamics and convection. This study improves our understanding of the importance of aerosol heating rate over the IGB region because it can alter the temperature and modify the monsoon.…”
mentioning
confidence: 99%